Autosomal recessive inheritance - Holden, Simon (Henry Stewart Talks, 2021)
Autosomal recessive disorders, Genetics, Inheritance, Cystic fibrosis, Sickle cell anaemia, Thalassaemia, Genetic disorders, Population biology